Revitalización urbana con enfoque táctico y ecológico en el centro poblado Río Frío, Rivera-Huila - Alarcon Bautista, Juan Felipe (Universidad Antonio Nariño, 2024)
Río Frío, a population center located in the rural area of the municipality of Rivera - Huila, faces problems of informal development and lack of urban planning, which has led to structural disorganization, lack of facilities, deterioration of the road network, and scarcity of public space. This study justifies the need to intervene through a tactical and ecological urban planning approach to improve the quality of life, generate employment, and attract investment, mainly benefiting local inhabitants and potential tourists and investors. The overall objective is to revitalize the area and enhance its tourist and economic attractiveness through specific strategies that include the analysis and characterization of the territory, and the implementation of infrastructure improvements in addition to increasing areas of public space. The methodology contemplates a detailed urban and territorial analysis, followed by intervention proposals based on citizen participation and sustainability, in order to transform Rio Frio into a model of sustainable urban development, an attractive tourist and investment destination. The scope of the project is limited by the lack of updated documentation and lack of community interest, but seeks to overcome these challenges through social cohesion and active participation of residents.